Effective sapphire repellency treatment to reduce fouling of a focused beam reflectance measurement (FBRM) probe in bituminous systems. (20th February 2019) - Saraka, Colin; Machado, Márcio B.; Webster, Scott E.; Gomez, Clara; Kresta, Suzanne M.
Abstract: The use of a focused beam reflectance measurement (FBRM) probe to track the chord length distribution dynamics in a bituminous system can be very challenging. Material coats the sapphire window of the probe and the quality of the data is compromised. The fouling index is a parameter used to assess the quality of the FBRM data. It is provided by the software and is the percentage similarity between two consecutive scans of the instrument, indicating how much of the reading has not changed due to material that is stuck to the optical window. When the FBRM was used in bitumen froth, the fouling index was higher than 90 %. In this work the significant reduction in fouling achieved with a sapphire repellency treatment is presented. The reduction in fouling was sufficient to detect broad trends in the FBRM data that will be used in future studies but was not sufficient to ensure quantitative measurement of the chord length distribution.